Science as Service : Establishing and Reformulating American Land-Grant Universities, 1865-1930 - Marcus, Alan I, 1949- (Book collections on Project MUSE., 2015)
Science as Service: Establishing and Reformulating American Land-Grant Universities, 1865-1930 is the first of a two-volume study that traces the foundation and evolution of America's land-grant institutions. In this expertly curated collection of essays, Alan I Marcus has assembled a tough-minded account of the successes and set-backs of these institutions during the first sixty-five years of their existence. In myriad scenes, vignettes, and episodes from the history of land-grant colleges, these essays demonstrate the defining characteristic of these institutions: their willingness to proclaim and pursue science in the service of the publics and students they serve. The Morrill Land-Grant College Act of 1862 created a series of institutions-at least one in every state and territory-with now familiar names: Michigan State University, Ohio State University, Purdue University, Rutgers University, the University of Arizona, and the University of California, to name a few. These schools opened educational opportunities and pathways to a significant segment of the American public and gave the United States a global edge in science, technical innovation, and agriculture. Science as Service provides an essential body of literature for understanding the transformations of the land-grant colleges established by the Morrill Act in 1862 as well as the considerable impact they had on the history of the United States. Historians of science, technology, and agriculture, along with rural sociologists, public decision and policy makers, educators, and higher education administrators will find this an essential addition to their book collections.